10th International Conference on Harmonics and Quality of Power. Proceedings (Cat. No.02EX630)
DOI: 10.1109/ichqp.2002.1221496
|View full text |Cite
|
Sign up to set email alerts
|

Equipment sensitivity to voltage sags-test results for contactors, PCs and gas discharge lamps

Abstract: Abslroct-Voltage sag tolerance levels were measured for samples of three equipment categories sensitive l o sags: C O I I~~C~O A , PCs and gas discharge lamps. An up-to-date voltage waveform generator was used to produce and repeat the evenu as necessary. Remaining voltage and sag duration were the test variables. For E O O~P C~O~S also the effect of paint-on-wave of sag initiation was studied. The resulu were rather well convergent with earlier studies by other institutes. This justifies more generalized eonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…The best immunity level was found to be 57% of nominal rms voltage. Different types of gas discharge lamp namely mercury, HPS and metal halide rated from 70 to 250 watts were exposed to voltage sags by Pohjanheimo and Lehtonen (2002). The study concluded that the mercury and HPS lamps are less sensitive to voltage sags than the metal halide ones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The best immunity level was found to be 57% of nominal rms voltage. Different types of gas discharge lamp namely mercury, HPS and metal halide rated from 70 to 250 watts were exposed to voltage sags by Pohjanheimo and Lehtonen (2002). The study concluded that the mercury and HPS lamps are less sensitive to voltage sags than the metal halide ones.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of PCs to voltage sags is addressed in several references in the past. Seven PCs of different ages were investigated for voltage sags (Pohjanheimo & Lehtonen, 2002). The malfunction criterion for the PCs selected was automatic reboot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to accurately evaluate the impact of voltage sags, the sensitivity of equipment and ultimately industrial processes to voltage sags must be known. The sensitivity curves of specific equipment have been intensively investigated [2][3][4], and a number of international standards have been set up to provide guidelines for system/tool design in terms of ride-through capability to voltage sags, such as the voltage tolerance curves recommended in IEEE 1346 [5]. From the customers' and equipment manufacturers' perspective, step-shaped ITIC curve [6], a successor of CBEMA curve, was proposed and recommended for use after extensive research in computer power supplies.…”
mentioning
confidence: 99%
“…Sags can drop out relays, contactors, and solenoids used in control systems [16], trip a dc-link, affect power components used in ASDs and programmable logic controllers (PLCs) [13,17], or trigger any fault-detection circuitry used in system and utilization equipment, resulting in disruptions and loss of data. Momentary interruptions can cause electronic equipment misoperation, shutdown, and, in some cases, damage.…”
Section: B Voltage Variationsmentioning
confidence: 99%